2019
DOI: 10.3389/fonc.2019.01133
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and MicroRNA Expression Patterns Between AML Patients With DNMT3A R882 and Frameshift Mutations

Abstract: Background: DNA methyltransferase 3A (DNMT3A) plays a unique role in hematopoiesis and acute myeloid leukemia (AML) pathogenesis. While the influences of DNMT3A mutation subtypes are still under debate.Purpose: Exploration of the clinical and molecular differences between AML patients carrying DNMT3A R882 mutations and DNMT3A frameshift mutations.Methods: Next generation of sequencing (NGS) and clinical data of 118 AML patients in our center were analyzed and compared. NGS, mRNA and miRNA profiling and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Yang et al indicated that there were different clinical features and disease prognoses in AML patients with different DNMT3A mutation types, which were related to unique miRNA expression patterns. Moreover, the expression level of three miRNAs (miR-10b, miR-143, and miR-30b) was decreased in the DNMT3A R882 group [ 29 ]. In the present study, DNMT3A mutation was obviously associated with age, blast in peripheral blood, and FLT3 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al indicated that there were different clinical features and disease prognoses in AML patients with different DNMT3A mutation types, which were related to unique miRNA expression patterns. Moreover, the expression level of three miRNAs (miR-10b, miR-143, and miR-30b) was decreased in the DNMT3A R882 group [ 29 ]. In the present study, DNMT3A mutation was obviously associated with age, blast in peripheral blood, and FLT3 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple researchers have confirmed that DNMT3A is frequently mutated in AML patients (13.5-23%) [3,93,94]. DNMT3A plays a unique role in hematopoiesis and AML pathogenesis as the inferior prognostic markers for AML patients [6,95]. For other non-R882 mutations, especially for DNMT3A frameshift mutations, the occurrence is much less frequent and its prognostic significance is poorly understood [6].…”
Section: Dnmt3amentioning
confidence: 99%
“…DNMT3A plays a unique role in hematopoiesis and AML pathogenesis as the inferior prognostic markers for AML patients [6,95]. For other non-R882 mutations, especially for DNMT3A frameshift mutations, the occurrence is much less frequent and its prognostic significance is poorly understood [6]. AML patients with DNMT3A truncating mutations have comparable prognoses to those of DNMT3A wild type patients [96].…”
Section: Dnmt3amentioning
confidence: 99%
See 2 more Smart Citations